Zosterops lateralis subsp. norfolkensis Mathews - , Mary (Zenodo, 2011)
Zosterops lateralis norfolkensis Mathews Zosterops lateralis norfolkensis Mathews, 1929: 10 (Near Kingston, Norfolk I.). Now Zosterops lateralis lateralis (Latham, 1801). See Mees, 1969: 30–70, Schodde and Mason, 1999: 687–691, van Balen, 2008: 467–468, and Checklist Committee, 2010: 309–310. HOLOTYPE: AMNH 701145 , adult male, collected near Kingston, 29.04S, 167.57E (Times Atlas), Norfolk Island, Australia, on 8 April 1913, by Roy Bell (no. 930). From the Mathews Collection via the Rothschild Collection. COMMENTS: In the original description, Mathews gave Bell’s unique field number of the holotype. Mathews’ collection had already been purchased by Rothschild when this subspecies was named, and Mathews listed the type as in the Rothschild Collection ‘‘ex Mathews Collection.’’ The Mathews Collection had held a large number of specimens collected on Norfolk in December 1912 through June 1913 by Bell, and all of these would have been available to Mathews in 1929; they were not entered in his catalog. Paratypes in AMNH are: AMNH 701138– 701144, 701146–701176 I did not find AMNH 701139 in the collection. : Published as part of Mary, 2011, Type Specimens Of Birds In The American Museum Of Natural History Part 9. Passeriformes: Zosteropidae And Meliphagidae, pp. 1-193 in Bulletin of the American Museum of Natural History 2011 (348) on page 30 : {"references": ["Mathews, G. M. 1929. [Mr. Gregory M. Mathews sent the following descriptions of new forms: -]. Bulletin of the British Ornithologists' Club 50: 10 - 11.", "Mees, G. F. 1969. A systematic review of the Indo- Australian Zosteropidae (Part III). Zoologische Verhandelingen 102: 3 - 390.", "Schodde, R., and I. J. Mason. 1999. The directory of Australian birds. Passerines. Collingwood, Victoria: CSIRO Publishing, 851 pp.", "van Balen, S. 2008. Family Zosteropidae (whiteeyes). In J. del Hoyo, A. Elliot, and D. Christie (editors), Handbook of birds of the world, vol. 13, Penduline-tits to shrikes: 402 - 485. Barcelona: Lynx Edicions, 879 pp., 60 pls., 536 photographs.", "Checklist Committee. 2010. Checklist of the birds of New Zealand, Norfolk and Macquarie islands, and the Ross Dependency, Antarctica, 4 th ed. Wellington: Te Papa Press, 500 pp., 4 maps."]}